(3GdGbJUGO aj GdGYJbGOs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3GdCScfOQjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ELJHi ef Uahg YHGOg YUGHI Cgd GdMb hCgd GdSfI , hNUge ef Hjf SGFQ GdaQb HeRGjG GddaX hGdefI s
(3BNQgG (B:s
(3hdfNJe GdcJGH HgPG abO CXgQfG GdEbJUGO ai GdEYJbGO , hMPafG GdMTh hGdaVhd GdeSJZfi Yfg Je GdcJGH s
(3fSNI YJjbIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B135s
Keywords: (3CUhd Gdabgs